2021
DOI: 10.1002/pca.3024
|View full text |Cite
|
Sign up to set email alerts
|

Determination of monosaccharides in Lycium barbarum fruit polysaccharide by an efficient UHPLC‐QTRAP‐MS/MS method

Abstract: Introduction Pre‐column derivatisation using 1‐phenyl‐3‐methyl‐5‐pyrazolone (PMP) is a common method for monosaccharide determination. Herein, a specific ultra‐high‐performance liquid chromatography quadrupole trap tandem mass spectrometry (UHPLC‐QTRAP‐MS/MS) method was developed and used for the determination of monosaccharide composition of Lycium barbarum polysaccharide (LBP). Objective Exploration of a new efficient method for monosaccharide determination. Methods In our study, hydrochloric acid was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The results of ultra-high-performance liquid chromatography quadrupole trap tandem mass spectrometry (UHPLC-QTRAP-MS/MS) showed that the LBP was composed of galactose, arabinose, mannose, rhamnose, xylose, ribose, and glucose, among which glucose was the most abundant monosaccharide [ 25 ]. As shown in Figure 1 , (1→3) -β-D-pyranogalactosyl, (1→4) -α-D-pyranogalactosyl residues, and (1→6) -β-D-pyranogalactosyl are three common characteristic structures [ 24 ].…”
Section: Bioinformatics Of Lbpsmentioning
confidence: 99%
“…The results of ultra-high-performance liquid chromatography quadrupole trap tandem mass spectrometry (UHPLC-QTRAP-MS/MS) showed that the LBP was composed of galactose, arabinose, mannose, rhamnose, xylose, ribose, and glucose, among which glucose was the most abundant monosaccharide [ 25 ]. As shown in Figure 1 , (1→3) -β-D-pyranogalactosyl, (1→4) -α-D-pyranogalactosyl residues, and (1→6) -β-D-pyranogalactosyl are three common characteristic structures [ 24 ].…”
Section: Bioinformatics Of Lbpsmentioning
confidence: 99%
“…An UHPLC system (Agilent infinity 1290, Agilent technologies) with a triple quadrupole-linear tandem with ion trap Mass Spectrometry detector (LC-MS/MS-API 4000 QTRAP from AB-Sciex) was used to analyse the sugar component (glucose and xylose). The method used was modified from Xu et al (2021). The liquid extract samples from non-treated and treated samples was evaporated at a temperature of 40C until dry and diluted using acetonitrile and water (ACN:water) 50:50, followed by homogenisation using vortex and sonicator.…”
Section: Sugar Determination (Uhplc-qtrap_ms/ms)mentioning
confidence: 99%
“…In recent years, polysaccharides have attracted much attention because of their complex structure and diverse biological activities, including antioxidant, antitumour, hepatoprotective, hypoglycemic, anti-bacterial, antiinflammatory and immunological activities. [2][3][4][5][6][7][8][9][10] Currently, the challenges of monosaccharide composition analysis (MCA) of polysaccharides are mainly reflected in the following aspects: (1) the complexity of polysaccharides makes it difficult to liberate monosaccharides completely; (2) inappropriate hydrolysis conditions may result in the degradation of released monosaccharides;…”
Section: Introductionmentioning
confidence: 99%
“…They widely exist in plants, animals, and microorganisms. In recent years, polysaccharides have attracted much attention because of their complex structure and diverse biological activities, including antioxidant, antitumour, hepatoprotective, hypoglycemic, anti‐bacterial, anti‐inflammatory and immunological activities 2–10 …”
Section: Introductionmentioning
confidence: 99%